A highly stable amino-coordinated MOF for unprecedented block off N2 adsorption and extraordinary CO2/N2 separation. Issue 93 (4th November 2016) - Zhang, Ling; Jiang, Ke; Jiang, Mengdie; Yue, Dan; Wan, Yating; Xing, Huabin; Yang, Yu; Cui, Yuanjing; Chen, Banglin; Qian, Guodong
Abstract : ZJU-198 for high CO2 /N2 separation and low isosteric heat. Abstract : A highly stable amino-coordinated metal–organic frameworkZJU-198 has been synthesized and structurally characterized, exhibiting high CO2 uptake of 105.8 cm 3 cm −3 while blocking off N2 adsorption at 1.0 bar and 298 K, attributed to the unique pore window sizes.